Geomechanical parameters in the active zone of an unsaturated tropical soil site via laboratory tests - Fernandes, Jeferson Brito [UNESP]; Saab, Alfredo Lopes [UNESP]; Rocha, Breno Padovezi; Rodrigues, Roger Augusto [UNESP]; Lodi, Paulo César [UNESP]; Giacheti, Heraldo Luiz [UNESP] (ABMS - Brazilian Association for Soil Mechanics and Geotechnical Engineering, 2022)
The seasonal variability of geotechnical parameters in the unsaturated zone is typically neglected in the design of geotechnical works. In most of the geotechnical projects the parameters are determined only for the saturated condition. Although it is known that this condition is the most critical to soil strength and deformability, this conservative approach may neglect a possible important contribution of the unsaturated condition, resulting in an increase in the cost of the geotechnical solution. This paper presents and discusses the site characterization of the active zone of an unsaturated sandy soil profile under different suction conditions. Laboratory tests with controlled suction (retention curves, triaxial compression with bender elements and oedometer tests) were carried out on undisturbed samples collected from 1.0 to 5.0 m depth. The results show that strength and deformability parameters are strongly affected by soil suction and are less influenced by confinement stress up to 5.0 m depth. All the investigated subsoil profile shows a collapsible behavior, more pronounced closer to the ground surface and under the effect of higher suction values. The findings highlight the importance of incorporating the suction influence in the site investigation, parameter determination, and geotechnical design for more economical, reliable, and environmentally sustainable solutions.
Keywords: Bender elements; Oedometer test; Suction; Triaxial compression test; Unsaturated soil